Analisis Pengaruh Kompensasi, Motivasi, Disiplin Kerja Terhadap Kinerja Karyawan Bimba Aiueo - Tukidi, Tukidi; Adhani, Ida; Emilya Sari , Desy Dwi (Management Research and Business Journal, 2024)
This research aims to determine the effect of compensation, motivation, work discipline on employee performance both partially and simultaneously. This research uses quantitative methods with data collection techniques through distributing questionnaires. In this study, a saturated sample was taken of all biMBA AIUEO employees with a population of 40 employees. The data analysis method used is multiple linear regression analysis, with analysis of the coefficient of determination (R2), t test, and F test. Multiple linear regression analysis produces the equation Y= 3.231 + 0.189X1 + 0.473X2 + 0.099X3 obtained a coefficient of determination (R2) value of 0.946 or 94.6%, meaning that the coefficient of determination of employee performance variables is explained by the variables compensation, motivation, work discipline. Meanwhile, the remaining 6.4% is explained by other variables not explained in this study. The results of the t test show that the compensation variable (X1) obtained t of 2.289 which is smaller than t 2.0280 with a significance level of 0.028 which is smaller than 0.05, the motivation variable (X2) obtained t of 4.495 which is greater than t 2.0280 with the level significant 0.000 is greater than 0.05, the work discipline variable (X3) obtained t of 1.202 is greater than t table 2.0280 with a significance level of 0.237 greater than 0.05. So the compensation variable (X1) has a partial effect on the employee performance variable (Y), the motivation variable (X2) has a partial effect on the employee performance variable (Y), the work discipline variable (X3) has a partial effect on employee performance (Y). The results of the F test show that the Fcount value of 210.631 is greater than the Ftable of 2.84 with a significant value of 0.00. The significance value is smaller than 0.05. This means that Ho4 is rejected and Ha4 is accepted, meaning that there is a simultaneous influence between compensation (X1), motivation (X2) and work discipline (X3) on the performance of biMBA AIUEO employees (Y).